Green Tea Polyphenol EGCG Alleviates Metabolic Abnormality and Fatty Liver by Decreasing Bile Acid and Lipid Absorption in Mice. Issue 4 (29th January 2018) - Huang, Jinbao; Feng, Simin; Liu, Anna; Dai, Zhuqing; Wang, Hong; Reuhl, Kenneth; Lu, Wenyun; Yang, Chung S.
Abstract : Scope: The tea polyphenol (‐)‐epigallocatechin‐3‐gallate (EGCG) has been shown to ameliorate metabolic abnormalities and fatty liver. The present study investigates the mechanisms of actions of EGCG on bile acid homeostasis and lipid metabolism. Methods: Male C57BL/6J mice are fed a low‐fat diet, a high‐fat western‐style diet, or a high‐fat western‐style diet containing 0.32% EGCG. The effects of the treatments on biochemical parameters, gene expression, and lipidomics are analyzed. Results: EGCG treatment significantly reduces body weight gain, mesenteric fat mass, fasting blood glucose, insulin resistance, serum cholesterol, and severity of fatty liver after treatment for 17 weeks, but most of these effects were less apparent at week 33. At week 17, EGCG treatment significantly elevates the mRNA levels of cholesterol 7α‐hydroxylase, HMG‐CoA reductase, low‐density lipoprotein receptor, and scavenger receptor B1, and partially normalizes the high‐fat diet induced lipidomic profile. The intestinal bile acid content is significantly decreased by EGCG, while fecal excretion of bile acids, cholesterol, and total lipids are increased. Conclusion: EGCG decreases bile acid reabsorption, results in lower intestinal bile acid levels, which further decreases the absorption of lipids. These actions contribute to the alleviation of metabolic abnormalities and fatty liver disease caused by the high‐fat diet. Abstract : The green tea polyphenol EGCG (0.32% in the diet) was found to reduce body weight gain, mesenteric fat mass, fasting blood glucose, insulin resistance, serum cholesterol, and severity of fatty liver in mice fed a high‐fat Western style diet. A proposed mechanism is that EGCG inhibits bile acid reabsorption and lipid absorption. EGCG also altered the gene expression of some key hepatic enzymes, resulting in partial alleviation of abnormal metabolism induced by the high‐fat diet.